Affinity development in undergraduate students at a large research institution - Berquam, Lori M., author; Kees, Nathalie, advisor; Banning, James, committee member; Brower, Aaron, committee member; Berry, Joyce, committee member (Colorado State University. Libraries, 2013)
Public institutions of higher education have faced repeated financial reductions over the past decade. The cumulative effect of reductions has necessitated public institutions re-examine funding models and funding alternatives that allow the institution to thrive. Alumni are the living endowment of the institution and are offered opportunities for involvement with their alma mater throughout their lives. The purpose of this study is to explore the association of specific university experiences that contribute to a strong sentiment of affinity of undergraduates for the institution. It further explores the experiences that appear to be most significant in developing university affinity at the undergraduate level. Current students enrolled at a public research extensive university in the Midwest were surveyed to determine if a relationship exists between university experiences and university affinity. This study also examined the differences in student characteristic information and university affinity. Using multiple regression to analyze the results, four university experience constructs were found significant. They include; student service opportunities, student service staff, initial impressions of the institution and extracurricular involvement. The analysis of student characteristics did not have significance in this study. Examining the experiences, perceptions and demographics of current students and what contributes to the concept of affinity is critical in the pursuit of alumni who want to be connected and committed to the institution.
Keywords: affinity; alumni; satisfaction; high impact practice